The Creativity of Adult PAK Services in the Church - Putri Amelia Siahaan; Damayanti Nababan (PT FORMOSA CENDEKIA GLOBAL, 2022)
I am interested in creativity in services, which in this journal I will explain, regarding service creativity in Adult PAK services, because creativity in Adult PAK services is needed to foster the spirit of serving Adults. The PAK Adult ministry also conducts teaching based on biblical theological knowledge. And through this theological knowledge, it can lead adults to live a good spiritual life, so that it has a positive impact on the church and society. The creativity of the PAK Adult ministry in the church is very influential on the development of the ministry of adults in the church, because most church members think that it is the adults in the church who will be the next generation of the church, so they really need souls who want to serve.